The Influence of Training on Nurse Performance at Class III Hospital 04.06.03 Dr. Soetarto Yogyakarta - Hodiri Adi Putra (Devitara Innovations, 2024)
Education and training (diklat) has a strategic role in improving the performance of quality human resources both in terms of abilities, skills and competencies. The purpose of this study is to determine the influence of training on the performance of nurses at TK III 04.06.03 Dr. Soetarto Yogyakarta Hospital. This research method is quantitative with the design of an analytical survey method with a cross-sectional approach. The sampling technique uses purposive sampling. The sample taken amounted to 59 people, namely nurses who were freelance daily workers (PHL) who had participated in Education and Training (Diklat) during their work. The analyses used were univariate and bivariate using the Chi Square test. The results of the analysis show that a p-value of 0.000 using an alpha value of 0.05 means that the p-value value is smaller than the alpha value of 0.000<0.05, thus there is a significant influence between training variables on nurse performance.